The Reaction of share prices to the announcements of right issues and debenture issues: evidence from a frontier market - Jayarathne, M.D.S.; Samarakoon, S. M. R. K.; Pradhan, R.P. (International Journal of Accounting & Business Finance, 2023)
Employing the event study methodology, this research probes the response of share prices to announcements of rights issues and debenture issues within the Colombo Stock Exchange. The market model, a quintessential tool for estimating abnormal returns, was harnessed to scrutinize samples encompassing rights issue announcements (n=85) and debenture issue announcements (n=106). These events transpired within the period spanning 2012 to 2019, providing a context post-Global Financial Crisis and pre-COVID-19 pandemic. The findings evince a notable negative reaction of share prices concurrent with the disclosure of rights issuance on the announcement day. Conversely, a non-significant positive reaction was observed for share prices on the debenture issue announcement date. The examination of the selected sectors' share price responses to both rights issue announcements and debenture issue announcements yielded mixed outcomes. Additionally, the results unveil a discrepancy with the semi-strong form of the market efficiency hypothesis, indicating the Sri Lankan Stock market does not adhere strictly to this theoretical proposition. Consequently, this study furnishes crucial insights into the dynamics of share price reactions in frontier markets like Sri Lanka, thereby contributing to the broader discourse on market efficiency
Keywords: Colombo Stock Exchange; Debenture Issue Announcements; Event Study; Right Issue Announcements; Market Model